2011
DOI: 10.1021/nn2028715
|View full text |Cite
|
Sign up to set email alerts
|

Growth Kinetics of Vertically Aligned Carbon Nanotube Arrays in Clean Oxygen-free Conditions

Abstract: Vertically aligned carbon nanotubes (CNTs) are an important technological system, as well as a fascinating system for studying basic principles of nanomaterials synthesis; yet despite continuing efforts for the past decade many important questions about this process remain largely unexplained. We present a series of parametric ethylene chemical vapor deposition growth studies in a "hot-wall" reactor using ultrapure process gases that reveal the fundamental kinetics of the CNT growth. Our data show that the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 49 publications
6
47
0
Order By: Relevance
“…When the H2 concentration is gradually increased to 35%, there is an evident decrease in the growth height of the VACNTs. It can be explained that excess hydrogen reacts with the carbon product during deposition, hindering the effective growth of CNTs [41]. These results show that VACNTs synthesized under a H2 concentration of 15% feature a good vertical orientation, and the tops of these arrays form small and homogeneous clusters.…”
Section: Morphological Analysis Of Vacntsmentioning
confidence: 87%
See 1 more Smart Citation
“…When the H2 concentration is gradually increased to 35%, there is an evident decrease in the growth height of the VACNTs. It can be explained that excess hydrogen reacts with the carbon product during deposition, hindering the effective growth of CNTs [41]. These results show that VACNTs synthesized under a H2 concentration of 15% feature a good vertical orientation, and the tops of these arrays form small and homogeneous clusters.…”
Section: Morphological Analysis Of Vacntsmentioning
confidence: 87%
“…In addition, maintaining a balance between carbon and hydrogen radicals in the reaction system is very important for CNT growth [40]. Insufficient hydrogen causes the oxidized catalyst Fe to be reduced incompletely, while excessive hydrogen converted the carbon production in the gas phase into the reagents, thus decreasing the overall driving force of the process [41]. Joshi et al [37,42,43] experimentally observed the role of water and hydrogen in terms of their influence on CNT growth, and point out that hydrogen controls the cracking of the carbon precursor ethylene, thereby controlling the purity as well as the number of walls of the CNTs grown.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the most common orientations of CNTs are displayed schematically in Figure 3. In general, films of vertically oriented carbon nanotubes exhibit much better electrical and capacitance properties in comparison to films formed from randomly oriented nanotubes [6,50,[54][55][56][57]. Figure 4 shows the structure of the SWCNT layer formed under CVD growth procedure.…”
Section: Capacitance Properties Of Single-and Multi-walled Carbon Nanmentioning
confidence: 99%
“…Especially, centimeter long CNT arrays are attractive for environmental sensor to monitor toxic chemicals and gases and for biomedical sensor to detect dopamine due to the excellent electrical, mechanical, electrochemical and thermal properties of CNT [6,[10][11][12][13]. There are variety of methods used to grow long, well-aligned CNT arrays such as oxygen assisted CVD, hot filament CVD, point arc plasma CVD, water assisted CVD, but most of them produce short CNTs (less than a few millimeters) [14][15][16][17][18][19][20][21][22][23]. Nevertheless, vertically aligned, centimeter long CNT arrays have rarely been reported since the window of growth conditions and catalyst composition is very narrow and the substrate design is challenging.…”
Section: Introductionmentioning
confidence: 99%